2022
DOI: 10.3390/agronomy12061338
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mapping of Soil Organic Matter and Cation Exchange Capacity in a Low Relief Landscape Using LiDAR Data

Abstract: Soil organic matter content (SOM) and cation exchange capacity (CEC) are important agronomic soil properties. Accurate, high-resolution spatial information of SOM and CEC are needed for precision farm management. The objectives of this study were to: (1) map SOM and CEC in a low relief area using only lidar elevation-based terrain attributes, and (2) compare the prediction accuracy of SOM and CEC maps created by universal kriging, Cubist, and random forest with Soil Survey Geographic (SSURGO) database. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…CEC of Sandwich compost substrate amended soil showed significantly greater than Sandwichcompost substrate unamended ones [52]. CEC was largely affected by the amount of organic matter [53][54][55] including Sandwich compost substrate. erefore, large percentages of organic matter contribute to more negative sites (e.g., lignin derivatives including humic-like substances) and thus, a high CEC value [56].…”
Section: Discussionmentioning
confidence: 99%
“…CEC of Sandwich compost substrate amended soil showed significantly greater than Sandwichcompost substrate unamended ones [52]. CEC was largely affected by the amount of organic matter [53][54][55] including Sandwich compost substrate. erefore, large percentages of organic matter contribute to more negative sites (e.g., lignin derivatives including humic-like substances) and thus, a high CEC value [56].…”
Section: Discussionmentioning
confidence: 99%
“…The Agronomy Center for Research and Education (ACRE) in Tippecanoe County, IN, USA (40°28′12″N, 86° 59′31″W) (Figure 1) was established in 1949 as a field research station for soils and crops research. As of 2020, it consisted of 570 ha (Rahmani et al., 2022). ACRE is located on a low relief, gently undulating Wisconsin age till plain and contains 14 different soil map units, with Chalmers (fine‐silty, mixed, superactive, mesic Typic Endoaquolls), Raub (fine‐silty, mixed, superactive, mesic Aquic Argiudolls), and Drummer (fine‐silty, mixed, superactive, mesic Typic Endoaquolls) soils as the dominant soil types.…”
Section: Methodsmentioning
confidence: 99%
“…The Agronomy Center for Research and Education (ACRE) in Tippecanoe County, IN, USA (40˚28′12″N, 86˚59′31″W) (Figure 1) was established in 1949 as a field research station for soils and crops research. As of 2020, it consisted of 570 ha (Rahmani et al, 2022) The tile lines at ACRE were typically installed at 0.9 m (3 ft) depth and at 20.16 m (66 ft) spacings. The lateral tile lines, which carry water from the fields to the larger main or submain tile lines, are typically 10 cm in diameter.…”
Section: Study Sitementioning
confidence: 99%
“…It was also found that 19% of the study area was not identified as valley bottom areas. The ability and performance of TWI as well as MrVBF in predicting soil organic matter (SOM) was also documented by Rahmani et al (2022).…”
Section: Static Covariatesmentioning
confidence: 98%